Sustainable Agroforestry Landscape Management: Changing the Game - Noordwijk, M. van; Speelman, E.; Hofstede, G.J.; Farida, A.; Abdurrahim, A.Y.; Miccolis, Andrew; Hakim, A.L.; Wamucii, C.N.; Lagneaux, E.; Andreotti, F.; Kimbowa, G.; Assogba, G.G.; et al. (MDPI, 2020)
Location-specific forms of agroforestry management can reduce problems in the forest–water–people nexus, by balancing upstream and downstream interests, but social and ecological finetuning is needed. New ways of achieving shared understanding of the underlying ecological and social-ecological relations is needed to adapt and contextualize generic solutions. Addressing these challenges between thirteen cases of tropical agroforestry scenario development across three continents requires exploration of generic aspects of issues, knowledge and participative approaches. Participative projects with local stakeholders increasingly use ‘serious gaming’. Although helpful, serious games so far (1) appear to be ad hoc, case dependent, with poorly defined extrapolation domains, (2) require heavy research investment, (3) have untested cultural limitations and (4) lack clarity on where and how they can be used in policy making. We classify the main forest–water–people nexus issues and the types of land-use solutions that shape local discourses and that are to be brought to life in the games. Four ‘prototype’ games will be further used to test hypotheses about the four problems identified constraining game use. The resulting generic forest–water–people games will be the outcome of the project “Scenario evaluation for sustainable agroforestry management through forest-water-people games” (SESAM), for which this article provides a preview.